Computing with large time steps in time-domain electromagnetics. Issue 17 (22nd November 2018) - Makwana, Nikitabahen N.; Chatterjee, Avijit
ABSTRACT: The finite volume time-domain method is recast in a large time step (LTS) version to solve the time-domain Maxwell's equations. The LTS method allows the use of time steps much larger than that dictated by the Courant–Friedrich–Lewy criteria for numerical stability in a Godunov-based finite volume framework. Solutions can be obtained much faster and sometimes with higher accuracy compared to conventional time-stepping methods. Results are analyzed for electromagnetic wave propagation in 1D and 2D. Solutions are shown to remain unconditionally stable with an increase in the Courant number.